Will it leak? Will it burst? COPV perforation and rupture after a MMOD impact. Issue 3 (September 2020) - Schonberg, William P.
Abstract: Most spacecraft have at least one pressurized vessel on board. Because of the serious damage that might result following a high-speed on-orbit space debris particle impact, a primary design consideration is the anticipation and mitigation of that damage. Depending on pressure vessel design and impact / operating conditions, a pressure vessel impacted at hypervelocity may experience either only relatively shallow damage; a through-hole, perhaps with localized liner cracking or composite peeling; or catastrophic failure (rupture). While a puncture and the resulting leak could de-stabilize an orbiting spacecraft, an on-orbit rupture could not only lead to spacecraft loss, but for human missions, possibly loss of life. Herein we present the development of a ballistic limit equation (BLE) and a rupture limit equation (RLE) for composite overwrapped pressure vessels. Similar to a BLE that can be used to characterize whether or not a pressure vessel would be punctured by a high-speed impact, an RLE is designed to differentiate between regions of operating and impact conditions that, given a perforation, would result in either a rupture or would result only in a relatively small hole or crack. In a risk assessment that considers the various failures that might occur following debris impact, both types of equations are required. Comparisons of the RLE and the BLE developed herein with experimental results shows that both equations are able to cleanly separate the regions of rupture from non-rupture, and perforation from non-perforation. As such, the equations presented are both highly accurate in predicting the response of the COPVs and impact conditions considered.